Modelling interdisciplinary collaboration to build cultural competence and academic literacy - Harvey, Arlene; Russell-Mundine, Gabrielle; Hoving, Eliot (Journal of Academic Language and Learning, 2016)
Universities across Australia are increasingly focussing on the ability of their students to engage with people from other cultures and to develop an understanding of Aboriginal and Torres Strait Islander knowledges and perspectives. This paper describes the collaborative aspect of a project aimed at supporting students’ development of cultural competence, which is part of a broader strategy at the University of Sydney to embed cultural competence in the curriculum across all faculties. The rationale for the focus on academic literacy practices is that students will be required to demonstrate cultural competence in assessment tasks, expressed in academic genres. One of our aims has been to identify the demands this places on students as they construct new disciplinary and cultural knowledge. Although our collaboration involves three areas – discipline knowledge, cultural competence and academic literacy – we focus here on the interrelationships between academic language and learning (ALL) practitioners’ and cultural competence specialists’ work. Based on insights drawn from our experience, we propose a new ‘Thirdspaces’ paradigm for supporting students’ cultural competence which highlights complementarities between our fields around epistemology and theory, and ways of working with discipline based teachers. While the main goal has been to transform the learning of students, our collaboration has given us the opportunity to learn and transform our own practices, providing a more solid foundation for future faculty embedding work around cultural competence. Our experience suggests that ALL units can play an important role in developing the cultural competence of students in our universities.